Best Proximity Point Theorems for Single and Multivalued Mappings in Fuzzy Multiplicative Metric Space. (3rd December 2021) - Farheen, Misbah; Kamran, Tayyab; Hussain, Azhar
Abstract : In this paper, we introduce fuzzy multiplicative metric space and prove some best proximity point theorems for single-valued and multivalued proximal contractions on the newly introduced space. As corollaries of our results, we prove some fixed-point theorems. Also, we present best proximity point theorems for Feng-Liu-type multivalued proximal contraction in fuzzy metric space. Moreover, we illustrate our results with some interesting examples.